India : Building Capacities for Public Private Partnerships - World Bank (Washington, DC, 2014)
This report concentrate on projects where private investment has been made, and where the government is either the purchaser of services under the project, or where it provides a financial contribution through direct investment or through risk bearing. The main sectors of focus are transportation (ports, airports, roads, and rail), water and sanitation and other urban infrastructure (solid waste management, light rail, bus terminals).